2009
DOI: 10.1264/jsme2.me08558
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Diversity and Symbiotic Effectiveness of Root-Nodulating Bacteria Associated with Cowpea in the South-West Area of Japan

Abstract: The phylogenetic diversity of cowpea root-nodulating bacteria in the South-West of Japan was investigated using 60 isolates. Seeds of cowpea were aseptically sown in vermiculite and inoculated with a suspension of Cowpea Soil (CS) or Bean Soil (BS) or without a soil suspension as a control. CS and BS were collected from the Kyushu University's farm (Japan) at sites where cowpea and bean, respectively, have been cultivated previously. Based on an analysis of the 16S rRNA gene and the Internal Transcribed Spacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
(27 reference statements)
2
12
0
2
Order By: Relevance
“…In this study, a high diversity of rhizobial strains was found nodulating cowpea and siratro, and this corroborates several studies that show a high heterogeneity in the populations of legumenodulating rhizobia (Sarr et al, 2009). Most of the isolates in this study were able to produce mucus, which might protect them to withstand temperature and pH fluctuations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, a high diversity of rhizobial strains was found nodulating cowpea and siratro, and this corroborates several studies that show a high heterogeneity in the populations of legumenodulating rhizobia (Sarr et al, 2009). Most of the isolates in this study were able to produce mucus, which might protect them to withstand temperature and pH fluctuations.…”
Section: Discussionsupporting
confidence: 90%
“…This reduces the positive effect of the microbial communities and increases the reliance on fertilizers to sustain any form of productive agriculture. According to microbehost specificity, rhizobia isolated from cowpea are generally placed in the cowpea-cross-inoculated group and species of this heterogeneous group were assigned, based on phylogenetic, to the genus Bradyrhizobium (Jordan, 1984;Sarr et al, 2009). On another hand, Siratro is a leguminous crop nodulated in its root system by all types of specific rhizobia in tropical soils with 70% of fast growing and 30% of slow growing rhizobia (Mwenda et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results in this study, B. yuanmingense is the most abundant endosymbiont isolated from cowpea nodules. This species represents 99 % of the strains isolated from cowpea in India (Appunu et al 2009), 94 % in Japan (Sarr et al 2009), 40 % in China (Zhang et al 2011), and35 % in Botswana (Steenkamp et al 2008). It is also widely distributed in Asia, Africa, and Latin America (Sarr et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This species represents 99 % of the strains isolated from cowpea in India (Appunu et al 2009), 94 % in Japan (Sarr et al 2009), 40 % in China (Zhang et al 2011), and35 % in Botswana (Steenkamp et al 2008). It is also widely distributed in Asia, Africa, and Latin America (Sarr et al 2009). In addition to cowpea, B. yuanmingense has been reported to form nodules in Phaseolus lunatus, a native legume of Peru (Ormeño-Orrillo et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…yuanmingense strains have also been isolated as dominant strainsfor mungbean in Nepal (Risal et al, 2012) and cowpea in Japan (Sarr et al, 2009). Several authors have isolated B. yuanmingense strains from soybean as a minor group in China (Man et al, 2008), Japan (Sarr et al, 2011),Nepal (Risal et al, 2010;Adhikari et al, 2012), Thailand (Maruekarajtinpleng et al, 2012), and Myanmar and Vietnam (Vinuesa et al, 2008;Soe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%